Efektivitas Pemberian Kompos Batang Pisang Kepok (Musa acuminata Colla) dalam Meningkatkan Pertumbuhan Bibit Kakao (Theobroma cacao L.) - Ansyori, Ansyori (AgriMalS, 2025)
This study evaluated the effectiveness of banana stem compost (Musa acuminata Colla) as a growth medium amendment to improve the early growth of cacao seedlings (Theobroma cacao L.). The experiment was arranged in a randomized complete block design with five media compositions—G0: soil+sand+compost (4:2:0); G1: soil+sand+compost (4:2:1); G2: (4:2:2); G3: (4:2:3); and G4: (4:2:4)—and five replications. Growth variables observed up to 14 weeks after transplanting included plant height, leaf number, maximum leaf area, stem diameter, root length, shoot fresh weight, root fresh weight, shoot dry weight, and root dry weight. ANOVA indicated highly significant effects of compost on plant height, maximum leaf area, stem diameter, shoot fresh weight, root fresh weight, shoot dry weight, and root dry weight; significant effects on leaf number; and non‑significant effects on root length. Mean separation using the Honest Significant Difference (HSD) test at 5% showed all compost treatments (G1–G4) outperformed the non‑compost control (G0) for height, shoot fresh weight, root fresh weight, and shoot dry weight. The medium with a 4:2:1 proportion (G1) was sufficient to achieve comparable performance to higher compost doses, indicating a practical and efficient recommendation for cacao nurseries. The results support the use of banana stem compost to enhance seedling vigor while potentially valorizing agricultural residues.